2014
DOI: 10.1155/2014/308286
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation andTH1/TH

Abstract: In recent times, human cell-based assays are gaining attention in assessments of immunomodulatory effects of chemicals. In the study here, the possible effects of cypermethrin and mancozeb on lymphocyte proliferation and proinflammatory (tumor necrosis factor (TNF-) α) and immunoregulatory cytokine (interferon- (IFN-) γ, interleukins (IL) 2, 4, 6, and 10) formation in vitro were investigated. Human peripheral blood mononuclear cells (PBMC) were isolated and exposed for 6 hr to noncytotoxic doses (0.45–30 µM) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…The robust association of RA with maneb/mancozeb is supported by a small body of experimental research on maneb immunotoxicity in vitro (Mandarapu et al 2014; Mandarapu and Prakhya 2015) and in vivo (Chung and Pyo 2005). Acute maneb immunotoxic effects in humans are thought to be limited (Corsini et al 2013), but chronic exposure has been associated with leukemia in a study of farm workers (Mills et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The robust association of RA with maneb/mancozeb is supported by a small body of experimental research on maneb immunotoxicity in vitro (Mandarapu et al 2014; Mandarapu and Prakhya 2015) and in vivo (Chung and Pyo 2005). Acute maneb immunotoxic effects in humans are thought to be limited (Corsini et al 2013), but chronic exposure has been associated with leukemia in a study of farm workers (Mills et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The AOX-generated IMI metabolites are not all regarded detoxification products IMI-NH is assumed to be a possible contributor to the nicotinic effects of IMI IMI-NH can become over 300 times more potent than IMI at the mammalian nAChR and when referring to mouse toxicity, it can also be increased many times as studies have shown [6,30,31] AOX is a potentially important factor in drug metabolism and ST treatments have provided a way to reduce AOX activity in vivo in mammals Frequent in vitro studies have revealed the contribution of cytochrome P450s and AOX in IMI oxidation and IMI reduction, respectively IMI is oxidized to the 5-hydroxy and olefin metabolites and reduced to the nitrosoguanidine, aminoguanidine and IMI-urea metabolites by human CYP isozymes [32,33] Nitroreduction reactions are possible also with rabbit liver cytosol independently of NADPH [34,32] AOX activity can be different between members of a single taxonomical species, or within a species, and can occur among species This intra-inter species variations could, therefore, affect the metabolism and detoxification processes of such neonicotinoids A study on rabbits by Stivaktakis [35] found that after a longer period of exposure to IMI than in our study, the genotoxic effect reached a plateau even in low dose groups, whereas we did not notice a plateau effect, but instead a noticeable MN increase, indicating a possible cumulative stressful effect that could lead to DNA damage with the CBPI index measured, however, to be lacking an overall cytotoxic effect for IMI and IMI+ST groups IMI, besides this study in rabbits, has also been studied in loaches for which IMI had a genetic toxic effect on erythrocytes [36], and on the Argentinian frog for which signs of genotoxicity were also present [37] Furthermore, the genotoxicity of IMI was found to have a potential adverse effect in human peripheral blood samples [38], but studying the relation of the metabolic activation and composition of a commercial product containing IMI on human peripheral blood samples did not show genotoxicity at a specific given dose [39] The oxidative as well as the inflammatory status of mammals exposed to neonicotinoid insecticides, such as IMI, have been studied often It is believed that insecticides affect the vital immune mechanisms and can induce various inflammatory conditions [40] Oxidative stress has been also studied in rabbits following long-term exposure to diazinon and propoxur, showing a discrete and concentration-dependent effect in the liver and kidney [41] Evaluation of the possible genotoxic and cytotoxic effects in human peripheral blood lymphocytes exposed in vitro to thiacloprid and clothianidin showed that at high concentrations they significantly reduced human lymphocyte viability and eventually caused cell death…”
Section: Discussioncontrasting
confidence: 53%
“…Monitoring inflammation can be achieved among others, either by measuring multifunctional pro-inflammatory cytokines, like TNF-α (tumor necrosis factor alpha), and interleukins (IL), a very sensitive but rather unspecific approach, or white blood cell count (WBC) and leukocyte subpopulations, such as PMBCs, proliferation and activity, aiming according to some researchers more to systemic inflammation [33] In our study, telomerase activity of CY compared to the control groups exhibits a significant increase in low and high dose groups CY exposure has previously been shown to increase cytokines in animal studies focusing on a-cypermethrin [34], a similar type synthetic pyrethroid of CY that we used, as well as on cypermethrin [35] on rats Interestingly enough, in a recent study [36] on interleukins and TNF cytokines in workers exposed to a-cypermethrin little or no changes in a white blood cell count (WBC) and leukocyte subpopulations were reported Effects of CY in human PBMCs were also evaluated in a study by Rajesh [37], where CY caused slight changes in cytokines, but no significant changes in proliferation Other studies focusing on carbamates pesticides, have also found an increase in systemic inflammation, as depicted by telomerase activity in PBMCs [38] To our knowledge, this is the first study to show that PBO exposure can also cause an increase in telomerase activity in PMBCs, for both low and high dose groups, even higher compared to the CY groups Such activation has a pivotal role to atheromatosis and coronary syndrome in humans, thus representing a very specific kind of inflammation [39] Up to now, studies in mice have linked inflammation due to PBO with induction of allergic reactions and dermatitis [40,41] Although PBO alone produces higher levels of telomerase activity compared to CY alone, their combination results in lower levels compared to the PBO alone This could be explained by the fact that when both the pesticide and the biocide are present, there is an interference in the action of CY, possibly by the designed mode of action of PBO that creates conditions that lead to CY's reduced metabolism and hence to reduced inflammatory contribution This would also explain why when PBO is administered alone there is more significant damage TBARS are byproducts of lipid peroxidation and when there are high levels of reactive oxygen species (ROS) an increase in lipid peroxidation is observed In the present study, TBARS were not affected significantly after either CY or PBO administration However, a study in Wistar rats showed that CY exposure can result in increased lipid peroxidation as measured in TBARS [42] Glutathione antioxidant system (GSH) plays an important role in cellular defense against reactive pro-oxidant products that have escaped decomposition by the antioxidant enzymes [43] Studies on rat erythrocytes showed that CY depletes GSH levels [32] However, our results showed no effect at any dose On the other hand, PBO caused a depletion compared to control groups in a dose dependent manner A study on fish [44] found that PBO likely inhibited the cytochrome P450 in a short-term exposure but in a long-term exposure the opposite was noticed Of note, glutathione S-transferase (GST) has been shown to be induced by PBO in Dro...…”
Section: Discussionmentioning
confidence: 98%
“…However, the analyses here were unable to define any immune system-related biological functions that were mediated through FEZ1 alone or in combination with other genes, based on network predictions using Genemania. Down-regulation of some of these transcription factors due to mancozeb or benzopyrene (positive control) exposure was likely a basis for previous observations showing there were significant changes in proliferation and T H 1/T H 2 cytokine (TNF, IFN, IL-2, IL-4, IL-6, IL-10) secretion by human peripheral blood lymphocytes (Mandarapu et al 2014). Further, the functional significance of these altered gene expressions may contribute to a multitude of immune cell-related functions/processes, including chemotaxis, migration, cell adhesion and motility, lymphocyte activation, immune cell migration, macrophage differentiation, platelet activation and apoptotic cell clearance/cell pathways/processes, due to mancozeb or benzopyrene (positive control) exposure.…”
Section: Discussionmentioning
confidence: 85%